СЕЗОННАЯ ДИНАМИКА ЧИСЛЕННОСТИ И КАЧЕСТВЕННОГО СОСТАВА ГЕМИПОПУЛЯЦИИ МЕТАЦЕРКАРИЙ ТРЕМАТОДЫ HELICOMETRA FASCIATA НА ЮГО-ЗАПАДНОМ ШЕЛЬФЕ КРЫМА - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2008)
Показано, что пространственно-временная и качественная гетерогенность гемипопуляции метацеркарий Helicometra fasciata в зарослевых биоценозах юго-западного шельфа Крыма обусловлены особенностями экологии основных промежуточных хозяев этой трематоды - черноморских скальных креветок Palaemon elegans. Несмотря на увеличение зараженности креветок с возрастом, основная часть метацеркарий Н. fasciata (в разные сезоны года - от 65 до 97 %) сосредоточена в годовиках P. elegans. В качестве хозяев геликометры более значимы самки P. elegans, аккумулирующие более 80 % пула личинок этой трематоды.
Seasonal dynamics of abundance and qualitative composition of trematode, Helicometra fasciata, metacercaria hemipopulation in coastal biocenosys of southwestern Crimea
Spatial and temporal heterogeneity of Helicometra fasciata metacercaria hemipopulation in coastal byocenosys of Sevastopol bays was studied and shown to be conditioned by ecological constraints of the second intermediate hosts of the digenean, shrimps Palaemon elegans. Mean intensity of shrimp's infection with metacercariae increases with host age. Nevertheless, the main part of H. fasciata metacercariae 65 - 97 %, depending of season) is accumulated in P. elegans of 1+ age. P. elegans females are more important as intermediate hosts, being accumulating more than 80 % of H. fasciata larvae pool.